Assessing the comparative effectiveness of ECHO and coaching implementation strategies in a jail/provider MOUD implementation trial - Todd Molfenter; Jessica Vechinski; Jee-Seon Kim; Jingru Zhang; Lionel Meng; Jessica Tveit; Lynn Madden; Faye S. Taxman (Implementation Science)
Abstract Background For nearly two decades, it has been widely recognized that individuals in jail settings have a high prevalence of opioid use disorders (OUD) and are highly susceptible to fatal overdose upon their release. This setting provides a public health opportunity to address OUD with Medication for Opioid Use Disorders (MOUDs). Yet, 56% of jails do not provide MOUD, creating a pressing need for better implementation approaches in jail and the hand-off to the community. Two successful implementation strategies, NIATx external coaching and the Extension for Community Healthcare Outcomes (ECHO) case management telementoring model, were compared to address this persistent treatment gap. Methods This 2 × 2 design compared high (n = 12) and low (n = 4) dose coaching with and without ECHO in a 12-month intervention and 12 M sustainability period. The national trial included 25 jails and 13 community-based partners. MOUD trends for buprenorphine, methadone, injectable naltrexone, and combined MOUD between the study arms were assessed. Results Jail sizes ranged from 24% with < 100 and 24% with > 500 daily population, and community-based treatment providers ranged from 63% with < 50 and 7% with > 500 average monthly OUD intakes. New patient counts were found to significantly increase across the intervention phase for buprenorphine (p < .01) and combined MOUD (p < .01). Injectable naltrexone and methadone showed no consistent, significant gains. For sites with low coaching without ECHO, new patient counts for combined MOUD were predicted to increase by 47.44% during the intervention phase and 7.30% during the sustainability phase. ECHO demonstrated that MOUD use did not significantly increase compared to coaching across MOUDs in the intervention phase (p = .517). High- and low-dose coaching showed no significant differences in MOUD use during the intervention phase (p = .124). Conclusions Coaching emerged as a more effective implementation strategy than ECHO for increasing buprenorphine use in jail settings. In practice, ECHO sessions offered considerable overlap with coaching strategies. While high-dose coaching had greater gains for MOUDs overall than low-dose coaching, those gains were statistically insignificant, suggesting low-dose coaching to be more economical. To increase MOUD use in jail settings, jurisdictions should focus on new MOUDs so all three MOUDs are available and enhance the post-incarceration continuum of care. Trial registration Name of registry: ClinicalTrials.gov. Trial registration number: NCT04363320. Date of registration: 2020–07-30. URL of trial registry record: https://clinicaltrials.gov/study/NCT04363320?term=molfenter&rank=7 .